Effect and Mechanism of Catalpol on Remyelination via Regulation of the NOTCH1 Signaling Pathway - Sun, Yaqin; Ji, Jing; Zha, Zheng; Zhao, Hui; Xue, Bing; Jin, Liangyun; Wang, Lei (Frontiers in Pharmacology, 2021)
Promoting the differentiation of oligodendrocyte precursor cells (OPCs) is important for fostering remyelination in multiple sclerosis. Catalpol has the potential to promote remyelination and exert neuroprotective effects, but its specific mechanism is still unclear. Recent studies have shown that the NOTCH1 signaling pathway is involved in mediating OPC proliferation and differentiation. In this study, we elucidated that catalpol promoted OPC differentiation in vivo and vitro and explored the regulatory role of catalpol in specific biomolecular processes. Following catalpol administration, better and faster recovery of body weight and motor balance was observed in mice with cuprizone (CPZ)-induced demyelination. Luxol fast blue staining (LFB) and transmission electron microscopy (TEM) showed that catalpol increased the myelinated area and improved myelin ultrastructure in the corpus callosum in demyelinated mice. In addition, catalpol enhanced the expression of CNPase and MBP, indicating that it increased OPC differentiation. Additionally, catalpol downregulated the expression of NOTCH1 signaling pathway-related molecules, such as JAGGED1, NOTCH1, NICD1, RBPJ, HES5, and HES1. We further demonstrated that in vitro, catalpol enhanced the differentiation of OPCs into OLs and inhibited NOTCH1 signaling pathway activity. Our data suggested that catalpol may promote OPC differentiation and remyelination through modulation of the NOTCH1 pathway. This study provides new insight into the mechanism of action of catalpol in the treatment of multiple sclerosis.